Enhanced intrinsic functional connectivity in the visual system of visual artist: Implications for creativity - Hong, Tzu-Yi; Yang, Ching-Ju; Shih, Chung-Heng; Fan, Sheng-Fen; Yeh, Tzu-Chen; Yu, Hsin-Yen; Chen, Li-Fen; Hsieh, Jen-Chuen (Frontiers in Neuroscience, 2023)
This study sought to elucidate the cognitive traits of visual artists (VAs) from the perspective of visual creativity and the visual system (i.e., the most fundamental neural correlate). This study examined local and the long-distance intrinsic functional connectivity (FC) of the visual system to unravel changes in brain traits among VAs. Twenty-seven university students majoring in visual arts and 27 non-artist controls were enrolled. VAs presented enhanced local FC in the left inferior temporal gyrus (ITG), left superior parietal lobule, left angular gyrus, and left middle occipital gyrus. VAs also presented enhanced FC with the ITG that targeted the visual area (occipital gyrus and cuneus), which appears to be associated with visual creativity. Learning-induced macroscopic neuroplasticity (appearing as a trait in VAs) can be attributed to the consolidation of consociated neural circuits, which are engaged in visual arts training and aesthetic experience. It appears that the visual creativity of VAs can be attributed to neurodynamic alterations in intrinsic connectivity in the visual system.